Factors contributing to information needs among students in UiTM Puncak Perdana / Mohd Asriq Lamit - Lamit, Mohd Asriq (Faculty Information Management, 2008)
The research is related with information needs among student. It will focus on students at UiTM Puncak Perdana. The research is about factors contributing to information needs among students in UiTM Puncak Perdana. From the Wikipedia, The Free Encyclopedia state that "information as a concept has a diversity of meanings, from everyday usage to technical settings. Generally speaking, the concept of information is closely related to notions of constraint, connmtnication, control, data, form, instruction, knowledge, meaning, mental stimulus, pattern, perception, and representation". From the definition, we know that information was use every time. As the student, we always closed with information by searching for our priority. What is information-literate? The American Library Association's (ALA) Presidential Committee on Information Literacy, Final Report states that, "To be information literate, a person must be able to recognize when information is needed and have the ability to locate, evaluate, and use effectively the needed information" (1989). From the definition, the student should know the when information is needed and they also able to search the location of information, know the value of information, and use the information effectively.